Determination of Water-Soluble Vitamins in Iraqi Honey Bee and Compare with Others Types by High –Performance Liquid Chromatography (Baghdad Science Journal, 2016)
High-performance liquid chromatographic methods are used for the determination of water-soluble vitamins with UV-Vis. Detector. A reversed-phase high-performance liquid chromatographic has been developed for determination of water-soluble vitamins. Identification of compounds was achieved by comparing their retention times and UV spectra with those of standards solution. Separation was performed on a C18 column, using an isocratic 30% (v/v) acetonitril in dionozed water as mobile phase at pH 3.5 and flow rate 1.0m/min. The method provides low detection and quantification limits, good linearity in a large concentration interval and good precision. The detection limits ranged from 0.01 to 0.025µg/ml. The accuracy of the method was tested by measuring average recovery values ranged between 94% - 101 %. For standerd solution, and 93%-99% of honey bee samples.